1996
DOI: 10.1099/00207713-46-2-460
|View full text |Cite
|
Sign up to set email alerts
|

Rubrobacter xylanophilus sp. nov., a New Thermophilic Species Isolated from a Thermally Polluted Effluent

Abstract: One strain of a thermophilic, slightly halotolerant bacterium was isolated from a thermally polluted industrial runoff near Salisbury, United Kingdom. This organism, strain PRD-lT (T = type strain), for which we propose the name Rubrobacter xylanophilus sp. nov., produces short gram-positive rods and coccoid cells and forms pink colonies. The optimum growth temperature is approximately 60°C. Unusual internal branchedchain fatty acids (namely, 12-methylhexadecanoic acid and 14-methyloctadecanoic acid) make up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 44 publications
(31 reference statements)
1
58
3
Order By: Relevance
“…In fact, T6P has been found to play important signaling roles in the regulation of sugar metabolism in Saccharomyces cerevisiae, by inhibiting hexokinase, and in Arabidopsis thaliana, where it activates ADP-glucose pyrophosphorylase (27). T6P is also a precursor of complex structures found in actinobacteria, such as mycolic acids, although R. xylanophilus lacks these trehalose-containing structures (5,35). The organization of the TreS and TreY/TreZ genes in a different and unique operon-like structure containing other genes for glycogen metabolism and the lack of activity in cell extracts from cultures grown on tryptone and yeast extract led us to hypothesize that these genes may be expressed only when maltose or maltooligosaccharides are used as carbon sources, as is the case with the TreS from Corynebacterium glutamicum (38).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, T6P has been found to play important signaling roles in the regulation of sugar metabolism in Saccharomyces cerevisiae, by inhibiting hexokinase, and in Arabidopsis thaliana, where it activates ADP-glucose pyrophosphorylase (27). T6P is also a precursor of complex structures found in actinobacteria, such as mycolic acids, although R. xylanophilus lacks these trehalose-containing structures (5,35). The organization of the TreS and TreY/TreZ genes in a different and unique operon-like structure containing other genes for glycogen metabolism and the lack of activity in cell extracts from cultures grown on tryptone and yeast extract led us to hypothesize that these genes may be expressed only when maltose or maltooligosaccharides are used as carbon sources, as is the case with the TreS from Corynebacterium glutamicum (38).…”
Section: Discussionmentioning
confidence: 99%
“…R. xylanophilus is a less intensively studied organism, although its genome sequence has recently been completed and it is of interest with regard to the mechanisms of radiation resistance (4, 10; http://genome .jgi-psf.org/finished_microbes/rubxy/rubxy.home.html). Moreover, the phylogenetic position of the subclass Rubrobacteridae is of interest, because this lineage may represent one of the earliest branches of the class Actinobacteria (4,16,17,30,48). Interestingly, our studies have shown that whereas T. fusca synthesizes a PGP-LTA, the cell envelope of R. xylanophilus appears to lack a macroamphiphile.…”
mentioning
confidence: 90%
“…The bacteria of the genus Rubrobacter represent the most ancient lineage of the phylum Actinobacteria (High G + C Gram-positive bacteria) known and are assigned to three known species, namely R. radiotolerans, R. taiwanensis and R. xylanophilus with optimum growth temperatures of 45, 55, and 60°C, respectively (Carreto et al 1996;Chen et al 2004;Suzuki et al 1988). All strains examined of Rubrobacter are gamma-radiation resistant and R. xylanophilus is, not only the most thermophilic actinobacterium known, but also the only true extremely radiation-resistant thermophile (Suzuki et al 1988;Ferreira et al 1999;Chen et al 2004).…”
Section: Introductionmentioning
confidence: 99%